WOMEN'S REPRESENTATION IN THE NOMINATION OF LEGISLATIVE MEMBERS ACCORDING TO LAW NUMBER 7 OF 2017 ON ELECTIONS - Fajar Irawan; Dhia Al-Uyun; Ngesti Dwi Prasetyo (RADJA PUBLIKA, 2023)
This scientific work focuses on the discussion of Women's Representation of at least 30% in the nomination of legislative members according to Law No. 7 of 2017 concerning Elections. In this work the author raised 2 (two) major discussions, the first related to the basis of consideration of women's representation of at least 30% in the legislative nomination and the second related to the legal implications of the rule. To answer these two discussions, the writer uses a normative juridical legal approach through the study of legal materials and sources of literature related to the theme that the writer adopts. From the results of this study the authors found several urgent issues that underlie the regulation of women's representation at least 30% in legislative nominations. The legal implications for election participants who do not obey these rules are disqualified from the electoral process in the electoral district concerned, these rules also serve as a legal umbrella against women who have not been accommodated in the political process. Although the rules related to women's representation have a positive impact on the life of politics in Indonesia, these rules need to be evaluated and refined to ensure women's representation.